2020
DOI: 10.1093/femsre/fuaa002
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of organohalide pollutant utilisation in bacteria

Abstract: Organohalides are organic molecules formed biotically and abiotically, both naturally and through industrial production. They are usually toxic and represent a health risk for living organisms, including humans. Bacteria capable of degrading organohalides for growth express dehalogenase genes encoding enzymes that cleave carbon-halogen bonds. Such bacteria are of potential high interest for bioremediation of contaminated sites. Dehalogenase genes are often part of gene clusters that may include regulators, acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 193 publications
0
9
0
Order By: Relevance
“…Preliminary experiments confirmed that DCM-degrading strain MC8b was also capable of growing with methanol, the reference growth substrate for strains of the Hyphomicrobium genus [32] to which strain MC8b had been tentatively affiliated [14]. We hypothesised that synthesis of the required dehalogenase to sustain strain MC8b growth on DCM may be regulated by the presence of its growth substrate, as observed in many dehalogenating strains [33]. Thus, we performed rapid differential proteomic analysis by pan-proteomics of cultures of the strain grown with either DCM or methanol.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Preliminary experiments confirmed that DCM-degrading strain MC8b was also capable of growing with methanol, the reference growth substrate for strains of the Hyphomicrobium genus [32] to which strain MC8b had been tentatively affiliated [14]. We hypothesised that synthesis of the required dehalogenase to sustain strain MC8b growth on DCM may be regulated by the presence of its growth substrate, as observed in many dehalogenating strains [33]. Thus, we performed rapid differential proteomic analysis by pan-proteomics of cultures of the strain grown with either DCM or methanol.…”
Section: Resultsmentioning
confidence: 59%
“…Indeed, the possibility of analysing differential abundance in the condition of interest compared to a reference condition represents a strong asset to identify proteins involved in a function of interest by pan-proteomics. In the field of bacterial dehalogenation, in particular, synthesis of the proteins involved in dehalogenation of a given organohalide often depends on its presence [33]. Identification of proteins of interest for a particular function will be more challenging when only one cultivation condition is available.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, Bio-RD-PAO opens up opportunities for complete attenuation and consequent effective in situ remediation of persistent organohalide pollution. formation results in their environmental prevalence (Fiedler, 2007;Sadowsky et al, 2013;Maucourt et al, 2020). Owing to their strong chemical stability, recalcitrance to degradation, global transfer and bioaccumulation and bioaugmentation via food webs, organohalides are raising concerns about their side effects on public health and ecosystems (Johnson-Restrepo B et al, 2005;Xu et al, 2006;Lu et al, 2019).…”
Section: $-mentioning
confidence: 99%
“…4 Integration of Bio-RD and PAO (Bio-RD-PAO) for extensive attenuation of organohalides 4.1 Bio-RD-PAO for complete removal of organohalides Both anthropogenic and natural sources of organohalides result in the wide distribution of massive amounts of organohalides in different environmental matrices (Xu et al, 2006;Maucourt et al, 2020). Particularly in anoxic subsurface environments, highly-halogenated organohalides (e.g., PCBs in commercial PCB mixture Aroclor 1260) need to be reduced first before their subsequent complete degradation via oxidative processes.…”
Section: $-mentioning
confidence: 99%
“…Strain DM4 and other bacteria that dehalogenate organohalides such as DCM have to cope with stresses associated with dehalogenation activity (intracellular increase in halides (e.g., Cl, Br, I) and acid production), organohalide toxicity (solvent stress), as well as changes in metabolic flux. Collectively, these stresses have a strong impact on gene regulation and the activity of regulatory factors, with extensive genome-wide modulation of gene expression [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%